GERMAS Policy Implementation and Low-Salt Diet Compliance Among Hypertensive Patients in Ratahan, North Sulawesi, Indonesia - Langingi, Ake Royke Calvin; Watung, Grace Irene Viodyta; Sepang, Mareyke Yolanda Lusia; Kairupan, Michelle (Journal of Health and Nutrition Research, 2026)
The aim of this study was to explore the relationship between the implementation of the “healthy living community movement” (GERMAS) policy and compliance with a low-salt diet among hypertensive patients. A quantitative cross-sectional study was conducted at Ratahan Primary Health Center among hypertensive patients who participated in the GERMAS program. Data were selected through proportional random sampling. Data were analyzed using multivariate logistic regression to determine the relationship between program implementation components, program socialization, community participation, and health facility support, and adherence to a low-salt diet. The analysis revealed that program socialization (OR=2.34, p=0.005, CI: 1.29–4.18), and has the most significant relationship of the other variables; community participation (OR=1.95, p=0.021, CI: 1.11–3.35), and health facility support (OR=2.07, p=0.017, CI: 1.14–3.68) were significantly associated with adherence to a low-salt diet. Implementation of GERMAS through effective program socialization, active community involvement, and adequate health facility support significantly increases adherence to a low-salt diet among hypertensive patients. Strengthening intersectoral collaboration and continuous community empowerment is crucial to sustaining GERMAS outcomes in hypertension prevention and control.